PERMANENT LEGAL STRENGTH (INKRACHT VAN GEWEIJSDE) PKPU PEACE IN BANKRUPTCY LAW - Poesoko, Felly Felmmy Dwi Renaningtyas; Susanti, Dyah Ochtorina; Tektona, Rahmadi Indra; Suci, Ivida Dewi Amrih; Astutik, Sri (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The decision to ratify PKPU peace (homologation) based on its regulations has permanent legal force (inkracht van geweijsde). The nature of permanent legal force is related to whether it can be executed or implemented immediately, so that this decision requires legal certainty by stating that the decision must have permanent legal force. Bankruptcy law regulates differently regarding the permanent legal force in PKPU decisions, the difference being that the permanent legal force does not apply to the entire substance of the case but only to the peace agreement agreement, which can be called limited permanent legal force. Regarding this specificity, the researcher wants to analyze it under the title